The biometric border world : - Olwig, Karen Fog; Grünenberg, Kristina; Møhl, Perle; Simonsen, Anja (Routledge Studies in Anthropology., 2020)
Since the 1990s, biometric border control has attained key importance throughout Europe. Employing digital images of, for example, fingerprints, DNA, bones, faces or irises, biometric technologies use bodies to identify, categorize, and regulate individuals' cross-border movements. Based on innovative collaborative fieldwork, this book examines how biometrics are developed, put to use and negotiated in key European border sites. It analyses the disparate ways in which the technologies are applied, perceived and experienced by border control agents and others managing the cross-border flow of people, by scientists and developers engaged in making the technologies, and by migrants and NGOs attempting to manoeuvre in the complicated and often unpredictable systems of technological control. Biometric technologies are promoted by national and supra-national authorities and industry as scientifically exact and neutral methods of identification and verification, and as an infallible solution to security threats. The ethnographic case studies in this volume demonstrate, however, that the technologies are, in fact, characterized by considerable ambiguity and uncertainty, and subject to substantial subjective interpretation, translation and brokering with different implications for migrants, border guards, researchers and other actors engaged in the border world -- Présentation de l'éditeur.